ANALISIS YURIDIS PERANAN PEMBIMBING KEMASYARAKATAN DALAM SISTEM PERADILAN PIDANA ANAK - IKSANTO, RIPRES (Dinamika Hukum, 2018)
The purpose of this study is to describe and analyze the role of social guidance in the process of settling the case of children and to know the obstacles that exist in the implementation of the tasks of the Counselor of Society. The research method consisted of: type of sociological juridical research, primary data source from observation, secondary data source from bibliography, relevant law and other regulation. Data analysis is done qualitatively. The result of the research shows that the role of the Social Supervisor in the investigation stage are: first, the Community Guidance makes the necessary Community Research as input material in the diversion process. Second, if the case is continued at the level of prosecution, the role of the Community Guardian is to assist the client (the suspect) when the person is handed over from the investigator to the prosecutor after the case is declared complete (P21). Furthermore, if the case is delegated to the district court, the role of the Social Supervisor following the proceedings of the trial and the results of Community Research is used as a consideration to take a decision (constraint) Barriers in the implementation of the role of Supervising Society is a factor limitation of operational resources, limited human resources both quantitative and ability in counseling. In addition, there is also limited infrastructure to support operations in the field. Keywords: Role of Community Guidance, Child Crime